#TITLE_ALTERNATIVE# - FIRMAN GHAZALI (NIM : 25113014), MOCHAMAD
The existence of industrial waste on the river stream and irrigation channels into paddy field area give an impact in decreasing quality of paddy field. The decreased process are influenced by the changes of soil pH value and that changes affect the heavy metal concentration and essensial mineral required by paddy is changed. The important of knowing soil pH particularly in paddy field, in this research is doing by making an estimation soil pH based on the spectral characteristics of each bands both of spectroradiometer and Landsat 8. The estimation method used for obtaining soil pH is regression model, calculated by correlating several soil pH acquired from field and soil samples analyzed in laboratory against reflectance numbers from each bands of Landsat 8, spectroradiometer, and several remote sensing indices derived from Landsat 8 such as normalized difference vegetation index (NDVI), soil moisture index (SMI), soil salinity index (SSI) and land surface temperature (LST), then it used to calculate soil pH distribution and it changes in paddy field. The final result of this research indicates the estimation value of soil pH based on remotely sensed data was done using the combinations of red and near infrared band, which produced of soil pH 5.3-5.9 and gives the accuracy 1.18 on the distribution of soil pH map respectively and brought to the change of paddy field quality based on soil pH changes to the more acid situation. The soil pH is validated using soil moisture index and soil salinity index and provide a positive linear with weak and moderate correlation respectively.